2005
DOI: 10.4028/www.scientific.net/msf.486-487.9
|View full text |Cite
|
Sign up to set email alerts
|

Gas Sensing Characteristics of ZnO-doped SnO<sub>2</sub> Sensors for Simulants of the Chemical Agents

Abstract: After the 9∙11 terrorism and America-Iraq war, apprehension of mass destruction weapons such as bio-chemical agents calls for much more sensitive sensors which can detect toxic gases. In this study, semiconductor gas sensors based on tin oxide were examined to detect chemical agent simulants: dimethyl-methyl-phosponate (DMMP), di(propylene glycol) methyl ether (DPGME), acetonitrile, and dichloromethane. DMMP((CH3O)3), DPGME(C7H16O3), acetonitrile(CH3CN), and dichloromethane(CH2Cl2) gases are the simulants of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…These details indicate the nanostructured metal oxides like TiO 2 , ZnO and MnO 2 may show sensitive and dissociative adsorbent of gas-phase DMMP at ambient temperature, promising sensing behavior for the mass detection of gas-phase organophosphorus compounds. However, only a few experimental studies have been reported on the adsorption of toxic chemicals or chemical warfare agent simulants on nano-structured MnO 2 at ambient temperature [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These details indicate the nanostructured metal oxides like TiO 2 , ZnO and MnO 2 may show sensitive and dissociative adsorbent of gas-phase DMMP at ambient temperature, promising sensing behavior for the mass detection of gas-phase organophosphorus compounds. However, only a few experimental studies have been reported on the adsorption of toxic chemicals or chemical warfare agent simulants on nano-structured MnO 2 at ambient temperature [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is interesting that the behavior of alumina-supported iron oxide may be significantly different from that of pure alumina [ 32 , 33 ]. Furthermore, zinc oxide doped in SnO 2 may improve the reliability and sensitivity of the SnO 2 sensors for simulants of the CWAs at 250 to 400 °C [ 40 ]. It is suggested that the absorption capability of DMMP on MnO 2 surface is possibly improved by ZnO modification.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, tin dioxide (SnO 2 ), an n-type semiconductor, has been the most investigated material for gas detection owing to its high sensitivity, rapid response time, low cost, and high chemical stability. [52,76,78,79,94,[113][114][115] As regards tin dioxide use for CWA simulant sensing, efforts have been initially devoted to thick films [5,27,47,52,64,76,78,79,83] and, subsequently, to 1D SnO 2 nanostructures, such as nanobelts, nanowires, and nanorods, [28][29][30]56,90,116] promising building blocks to develop a new generation of metal oxide gas sensors. As concerns the former, various literature works have reported on SnO 2 -based thick film, eventually mixed with Al 2 O 3 , In 2 O 3 , ZnO, ZrO 2 , Nb 2 O 5 , Pd, Pt, [27,47,78,117,118] Co 3 O 4 , Nb 2 O 5 , MoO 3 , NiO, Sb 2 O 3 , [52] or MoO 3 , Sb 2 O 3 , and NiO.…”
Section: Sno 2 -Based Sensorsmentioning
confidence: 99%
“…[52,76,78,79,94,[113][114][115] As regards tin dioxide use for CWA simulant sensing, efforts have been initially devoted to thick films [5,27,47,52,64,76,78,79,83] and, subsequently, to 1D SnO 2 nanostructures, such as nanobelts, nanowires, and nanorods, [28][29][30]56,90,116] promising building blocks to develop a new generation of metal oxide gas sensors. As concerns the former, various literature works have reported on SnO 2 -based thick film, eventually mixed with Al 2 O 3 , In 2 O 3 , ZnO, ZrO 2 , Nb 2 O 5 , Pd, Pt, [27,47,78,117,118] Co 3 O 4 , Nb 2 O 5 , MoO 3 , NiO, Sb 2 O 3 , [52] or MoO 3 , Sb 2 O 3 , and NiO. [79] In these cases, sensing devices were manufactured via screen-printing, and their properties were tested toward the detection of DMMP, di(propylene glycol) monomethyl ether (DPGME), acetonitrile (ACN), and DCM.…”
Section: Sno 2 -Based Sensorsmentioning
confidence: 99%
See 1 more Smart Citation